Perceived quality of care for severe acute malnutrition management among caregivers of under-five children with severe acute malnutrition in Addis Ababa, Ethiopia, 2022: a mixed-method study - Adema, Bulcha Guye; Atnafu, Niguse Tadele; Ashagre, Feven Mulugeta (Frontiers in Public Health, 2023)
Introduction All the factors at the institutional, provider, and client levels have an impact on the quality of care. In low- and middle-income countries, poor quality of severe acute malnutrition (SAM) management at health institutions is a major contributor to child morbidity and mortality. This study aimed to determine the perceived quality of care for SAM management among caregivers of under-five children. Methods This study was conducted in public health facilities that provide inpatient SAM management in Addis Ababa, Ethiopia. An institution-based convergent mixed-method study design was implemented. Quantitative data were analyzed by using a logistic regression model, while thematic analysis was used to analyze the qualitative data. Results A total of 181 caregivers and 15 healthcare providers were recruited. The overall perceived quality of care for SAM management was 55.80% (CI: 48.5–63.10). Urban residence (AOR = 0.32, 95% CI: 0.16–0.66), college and above level education (AOR = 4.42, 95% CI: 1.41–13.86), working as a government employee (AOR = 2.72, 95% CI: 1.05–7.05), readmitted to the hospital (AOR = 0.47, 95% CI: 0.23–0.94), and length of hospital stays >7 days (AOR = 2.1, 95% CI: 1.01–4.27) were found to be significantly associated factors with perceived low-quality care for SAM management. Additionally, lack of support and attention from higher levels of management, and lack of supplements, separate units, and laboratory facilities were among the factors that impede the provision of quality care. Discussion Perceived quality of SAM management services was low against the national goal of quality improvement to meet the expectations of both internal and external clients. Rural residents, those with more educational qualifications, government employees, newly admitted patients, and patients who stayed longer in hospitals were the most unsatisfied groups. Improving support and logistic supply to health facilities, providing client-centered care, and responding to caregivers' demands may help to improve quality and satisfaction.